(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the use of artificial intelligence (AI) technologies in the process of professional teacher training. The study is presented in the form of a critical analysis of international scientific literature, based on the works of seven major researchers. It thoroughly explores the current state of AI in education, its opportunities and challenges in teacher training. The results of the study indicate that artificial intelligence can serve as an effective tool for personalizing education, implementing differentiated instruction, and enhancing professional competence. However, ethical issues, data privacy, and the need to improve digital literacy among teaching staff remain pressing challenges.